Integrated Fast Assembly of Free-Standing Lithium Titanate/Carbon Nanotube/Cellulose Nanofiber Hybrid Network Film as Flexible Paper-Electrode for Lithium-Ion Batteries - Cao, Shaomei; Feng, Xin; Song, Yuanyuan; Xue, Xin; Liu, Hongjiang; Miao, Miao; Fang, Jianhui; Shi, Liyi (ACS applied materials & interfaces, 2015)
A free-standing lithium titanate (Li4Ti5O12)/carbon nanotube/cellulose nanofiber hybrid network film is successfully assembled by using a pressure-controlled aqueous extrusion process, which is highly efficient and easily to scale up from the perspective of disposable and recyclable device production. This hybrid network film used as a lithium-ion battery (LIB) electrode has a dual-layer structure consisting of Li4Ti5O12/carbon nanotube/cellulose nanofiber composites (hereinafter referred to as LTO/CNT/CNF), and carbon nanotube/cellulose nanofiber composites (hereinafter referred to as CNT/CNF). In the heterogeneous fibrous network of the hybrid film, CNF serves simultaneously as building skeleton and a biosourced binder, which substitutes traditional toxic solvents and synthetic polymer binders. Of importance here is that the CNT/CNF layer is used as a lightweight current collector to replace traditional heavy metal foils, which therefore reduces the total mass of the electrode while keeping the same areal loading of active materials. The free-standing network film with high flexibility is easy to handle, and has extremely good conductivity, up to 15.0 S cm–1. The flexible paper-electrode for LIBs shows very good high rate cycling performance, and the specific charge/discharge capacity values are up to 142 mAh g–1 even at a current rate of 10 C. On the basis of the mild condition and fast assembly process, a CNF template fulfills multiple functions in the fabrication of paper-electrode for LIBs, which would offer an ever increasing potential for high energy density, low cost, and environmentally friendly flexible electronics.